The Relation of Physics Teaching Materials to Higher Education Objectives - Cahyadi, Dadi; Indra, Hasbi (Formosa Journal of Sustainable Research, 2024)
This study examines the dominance of the positivistic perspective in science education at universities, which often separates natural science from faith-based values. To bridge this gap, developing a Physics textbook that integrates a faith-based approach becomes crucial. This learning resource aims to teach Physics scientifically while connecting it with students' spiritual values.  The research explores the alignment of university Physics education with broader educational goals, employing qualitative methods including literature reviews and textbook analysis. Findings reveal that most Physics textbooks lack integration of spiritual and faith-based values. Consequently, this study proposes a concept for interdisciplinary Physics teaching materials that harmoniously integrate scientific and faith-based values. It also includes discussions on Islamic epistemology, addressing recognised sources and methods of knowledge in Islam, fostering graduates proficient in Physics with strong faith foundations